Pemanfaatan Prompt AI untuk Guru Sekolah Dasar Islam Terpadu Lukmanul Hakim Kecamatan Puring Kabupaten Kebumen (Lembaga Pengembangan Kinerja Dosen, 2026)
The advancement of Artificial Intelligence (AI) presents substantial potential for improving the quality of learning in elementary education, particularly through the application of AI prompts as instructional support in lesson planning and classroom implementation. Nevertheless, many teachers at Integrated Islamic Elementary Schools (Sekolah Dasar Islam Terpadu/SDIT) experience limited AI literacy and insufficient competence in designing pedagogically appropriate and effective AI prompts. This community service program aims to enhance AI literacy and strengthen the professional competence of teachers at SDIT Lukmanul Hakim Puring, Kebumen, in utilizing AI prompts to support instructional design, teaching materials development, and learning assessment. The program employed participatory methods, including socialization sessions, hands-on training, guided practice, and continuous mentoring. The results demonstrate a measurable improvement in teachers’ understanding and practical skills in constructing AI prompts aligned with pedagogical objectives. Furthermore, the integration of AI prompts contributes to increased instructional efficiency and pedagogical creativity. This program is expected to provide a sustainable model for supporting digital transformation in elementary school education.